THE ROLE OF PHYSICAL EDUCATION PEDAGOGUES WORKING WITH PRE-SCHOOLERS - Dževad Džibrić; Alija Biberović; Tarik Huremović; Jasmin Bilalić (Sport Scientific And Practical Aspects, 2025)
Preschool education is socially organized and along with family education makes a unique entity. Its character is social, since the care for children’s development and education in their early age is essential for society prosperity. During this period important role makes health and physical education, realized through children’s physical activity. It presents foundation of physical and health education which has to devote adequate attention. During this period it is necessary to add organized physical activity – exercise to natural instincts, which will carve an image of physical and health education into child’s mind during their early age. This way a child will acquire knowledge of inevitable participation in physical activities and forms the sense of satisfaction while exercising and playing. The objective of this work is to present the role of physical and health education pedagogues in their work with preschool children. Realization of program tasks in physical and health education in this age can not be maintained without involvement of physical and health education pedagogues. Physical and health educator is an essential factor and subject of teaching process. Even well prepared applications, nor the best working conditions, which are very important, do not represent anything, if teacher of physical and health education, is not doing his job properly.